HUBUNGAN POWER OTOT LENGAN BAHU DAN KELENTUKAN OTOT PUNGGUNG TERHADAP HASIL SMASH PUTRA PERSATUAN BULUTANGKIS BHINEKA MAJAPAHIT TAPUNG KAMPAR - Pungki, Muhammad Galang; Ramadi, Ramadi; Sulastio, Agus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The aim of this research was to determine the existence of the correlation between the strength of the shoulder arm muscle and the back muscle flexibility and to demonstrate this on the results of the men's mashmunie union Bhineka Majapahit Tapung Kampar. The type of research performed in this research is the use of a correlational research design that seeks to determine the correlation between the independent variable, the strength of the shoulder muscles and the flexibility of the back muscles, and the dependent variable the ability to break. The population in this riset has no fewer than 8 people, given the small number of samples, namely fewer than 30 people, in this research used a saturated sampling technique of a total of 8 people. Saturated sampling is a sampling technique when all members of the population are used as samples. This is often done if the population is relatively small, fewer than 30 people, or research that wants to make generalizations with very small errors. Another term for saturated monsters is the census, which includes all members of the population. Of the results obtained by the strength of the shoulder arm muscle there is a connection with the results of the smash in the game Badminton Bhineka Majapahit Tapung Kampar, namely the acquisition of rcount (0.98)> of the acquisition of rtable (0.754) on α = 0.05. From the results obtained by the back muscle flexibility there is a connection with the results of the smash on badminton, namely the acquisition of rcount (0.90)> of the acquisition of rtable (0.754) at α = 0.05. There is a joint correlation between shoulder arm muscle strength and back muscle flexibility on the results of the Bhineka Majapahit Tapung Kampung rcount (0.980) of the men's badminton association> of the acquisition of rtable (0.754) at α = 0.05. Key Words: Strength Of Shoulder Arm Muscles, Flexibility Of Back Muscles, Smashes, Badminton.